Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1977
DOI: 10.1139/x77-067
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of the oleoresin system of the four major southern pines

Abstract: Oleoresin viscosity, flow (rate, duration, and total amount), and rate of crystallization were determined for Pinuselliottii Engelm., Pinuspalustris Mill., Pinustaeda L., and Pinusechinata Mill, in central Louisiana, U.S.A. Physical properties of the oleoresin and tree morphological characteristics (diameter at breast height, growth rate, height, crown ratio, and age) were not strongly related in either of the four species. Pinuselliottii oleoresin was extremenly viscous, crystallized very slowly, and flowed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 0 publications
1
23
1
2
Order By: Relevance
“…Mean yield for Harrison 2 was less than 0.5 g, whereas mean values for the loblolly and longleaf stands investigated were higher, reaching magnitudes greater than 2.0 g for several stands (Table 2). This pattern agrees with results reported by Hodges et al (1977), who found that slash pine had a lower mean resin yield than the other major southern pines when yields were evaluated 8 h following wounding. Despite low mean yield and low phenotypic variance, the repeatability estimate for this stand is only slightly lower than the values obtained for the loblolly stands, and intermediate to those determined for the longleaf stands.…”
Section: Repeatability Determinationssupporting
confidence: 92%
“…Mean yield for Harrison 2 was less than 0.5 g, whereas mean values for the loblolly and longleaf stands investigated were higher, reaching magnitudes greater than 2.0 g for several stands (Table 2). This pattern agrees with results reported by Hodges et al (1977), who found that slash pine had a lower mean resin yield than the other major southern pines when yields were evaluated 8 h following wounding. Despite low mean yield and low phenotypic variance, the repeatability estimate for this stand is only slightly lower than the values obtained for the loblolly stands, and intermediate to those determined for the longleaf stands.…”
Section: Repeatability Determinationssupporting
confidence: 92%
“…Since insects take oxygen into their bodies through pleural spiracles (lateral aperatures) along the thorax and abdomen, immersion of bark beetles in oleoresin may have a suffocating as well as a toxic effect. Hodges et al (1977Hodges et al ( , 1979 reported that the resistance of four native pine species in the southeastern US to colonization by D. frontalis was strongly related through a discriminant analysis to physical properties of the oleoresin such as total flow, flow rate, viscosity, and time to crystallization.…”
Section: Monoterpenes Pine Defenses and Effects On Bark Beetle Physmentioning
confidence: 99%
“…Only one sample per tree was taken per sampling period to avoid placing undue stress on active cavity trees. Because of the co-occurrence of loblolly and shortleaf pine cavity trees in woodpecker clusters on the clayey shrink-swell soils, as well as the similarity of those pine species in susceptibility to bark beetle infestation and magnitudes of resin production (Hodges et al 1977), loblolly and shortleaf pine trees were considered as a single group for measurements of resin production and bark beetle mortality.…”
Section: Fig 2 Band-sharing Among Putative Carolinamentioning
confidence: 99%
“…Although the difference is not statistically significant, it is important to note that active longleaf pine cavity trees were killed by bark beetles at 1.3 times the rate of inactive loblolly and shortleaf pine cavity trees ( 2 ϭ 0.322, P ϭ 0.57). Usually, longleaf pines are much more resistant to bark beetle infestation than loblolly and shortleaf pines (Hodges et al 1977). Because of their greater vulnerability to bark beetle infestation, population levels of southern pine beetles were higher in loblolly shortleaf pine habitat (x ϭ 97.0 Ϯ 82.6 bark beetle spots) than in longleaf pine habitat (x ϭ 16.2 Ϯ 20.2) throughout the study (t ϭ 3.54, df ϭ 24, P ϭ 0.003, see also Schaefer 1996).…”
Section: Fig 1 Resin Yield Versus the Number Of Years Cavity Trees mentioning
confidence: 99%